2015
DOI: 10.1007/s10530-015-0935-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of insect invasions in North America, Japan and their Islands

Abstract: Among the various animal taxa that are have established outside their native ranges, invasions by insect species are the most numerous worldwide. In order to better understand the characteristics of insect species that make them more invasion prone, the characteristics of habitats that make them more susceptible to invasions and to understand the pathways that facilitate invasions, we compared the compositions of the native and non-native insect communities among five Pacific regions: North America, the Hawaii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…For example, of the ~90 000 insect species native to North America, only 55 have successfully invaded Japan (Yamanaka et al . ). Despite the seemingly endless supply of species in source regions, there is reason to believe that depletion of species pools has had at least some effect on rates of species establishment.…”
Section: Discussionmentioning
confidence: 97%
“…For example, of the ~90 000 insect species native to North America, only 55 have successfully invaded Japan (Yamanaka et al . ). Despite the seemingly endless supply of species in source regions, there is reason to believe that depletion of species pools has had at least some effect on rates of species establishment.…”
Section: Discussionmentioning
confidence: 97%
“…We censused non‐native insects, using published lists (Aukema et al, ; Yamanaka et al, ), and identified 58 conifer specialists currently established in North America that feed on hosts in Cupressaceae, Pinaceae, and/or Taxaceae (Table A1). For each conifer specialist, literature and online searches were conducted (March 2016–July 2017) to find: (a) values of 15 potentially relevant insect life history traits including fecundity and voltinism, (b) the highest level of plant damage described in published literature, (c) all documented North American host trees (excluding conifers outside their native range in North America), and (d) all host trees from the insect's native range.…”
Section: Methodsmentioning
confidence: 99%
“…We censused non-native insects, using published lists (Aukema et al, 2010;Yamanaka et al, 2015), and identified 58 conifer specialists currently established in North America that feed on hosts in Cupressaceae, Pinaceae, and/or Taxaceae (Table A1) High-impact insects were defined as those reported to cause tree mortality at the population or regional level (Figure 1), whereas species that directly or indirectly caused only individual tree mortality or minor damage were not considered to be high impact (Table 1). A binary impact response variable was considered useful for decisionmaking (high impact or not), avoided the subjectivity of multiple impact levels, and eliminated the potential effect of time since introduction.…”
Section: Insect Traitsmentioning
confidence: 99%
“…For these, the country in which they originally evolved is probably of limited importance when considering invasion pathways. Such species could have reached Hawaii from any part of their disrupted distribution, although Yamanaka et al (2015) appeared to assume that each invasive species had entered Hawaii from the area in which it had evolved. Despite this, an invasion pathway from the Americas is indicated by the 15 species that are found otherwise only in North America, and a second pathway is indicated by the five species shared only with the Neotropics.…”
Section: Biology Of Thysanopteramentioning
confidence: 99%